2017
DOI: 10.18280/ijht.35sp0157
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the climatic condition on the radiant asymmetry

Abstract: This paper analyzes the influence of solar radiation, considering both its direct and diffuse component, on the local thermal comfort of subjects in indoor environments. In fact, as well as too hot or too cold climatic conditions may cause global thermal discomfort, an unwanted cooling or heating of a particular confined area of the body may cause local thermal discomfort, which may occur for vertical air temperature differences, unsuitable temperatures of the floor, drafts and radiant asymmetries. In this con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 16 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…In a heating situation, they found that solar radiation indoors could save up to 40% annual heating energy. Marino et al [ 27 ] also conducted an experimental test to explore the radiant asymmetry caused by solar radiation, doing the measurements at only one point indoors. The results show that the radiant asymmetry by solar radiation was much stronger than those by interior building surfaces like walls, ceilings, and floors.…”
mentioning
confidence: 99%
“…In a heating situation, they found that solar radiation indoors could save up to 40% annual heating energy. Marino et al [ 27 ] also conducted an experimental test to explore the radiant asymmetry caused by solar radiation, doing the measurements at only one point indoors. The results show that the radiant asymmetry by solar radiation was much stronger than those by interior building surfaces like walls, ceilings, and floors.…”
mentioning
confidence: 99%